The Effect of Training Methods and Eye-Foot Coordination on Football Passing Accuracy - Thomas, Angga; Rustiadi, Tri; Hartono, Mugiyo (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The problem of low level of passing ability. The purpose of analyzing the training method and eye-foot coordination and analyzing the interaction between the passing training method and eye-foot coordination. This study used a quasi-experimental approach with pre- and post-tests. Population 36 players with an average age of 16 years. Total sampling was employed with a sample size of 36 players, and data analysis using the ANOVA test. 1. There is a difference in the effect of fixed target and moving target passing practice on soccer passing accuracy, average of (82.78±7.51), p-value of (0.000<0.05), and Fcount value of (18,050) > Ftable (0.225). 2. Sig p-value = (0.007< 0.05) and Fcount (8.450) > Ftable, there is a difference in the effect of high and low eye-foot coordination on soccer passing accuracy (0.225). 3. There significant difference in the Effects of Fixed Target Passing Training Methods with High and Low Eye-foot Coordination on Football Passing Accuracy, an average value of (83.33> 67.78). 4. There is a significant difference in the effect of moving target passing exercises requiring high and low eye-foot coordination on soccer passing accuracy, average value of (85.56>80.00). 5. There is no effect of training methods or eye-foot coordination on soccer passing accuracy, with sig p-value = (0.053>0.05) and Fcount (4.050) > Ftable (0.225). Conclusion: moving target passing activities are more effective in improving passing accuracy than fixed target passing exercises, and players with a high eye-foot coordination have greater accuracy than players with a low eye-foot coordination.